Teknik Behavioral Reherasal Terhadap Peningkatan Tanggung Jawab Belajar Di Era Pandemi Covid-19 - Susmawati Surya Asih Susmawati Surya Asih; Purwati Purwati; Sugiyadi Sugiyadi (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
Testing the effect of group counseling with behavioral rehearsal techniques on increasing student learning responsibilities in the era of the covid-19 pandemic is the purpose of this study, one group pretest and posttest designs were used in this study. The sampling technique used in this study was purposive sampling, namely the Sarbini Grabag Islamic Junior High School students who had low learning responsibility characteristics using a sample of 8 people. It is carried out by using a learning responsibility questionnaire on the data collection method. Parametric analysis of paired sample t-test was used in the data analysis method. This research has succeeded in proving that group counseling with behavioral rehabilitation techniques has an effect on increasing learning responsibilities in the era of the covid-19 pandemic. The results of the paired sample t test are proven by the probability value of sig(2-tailed) 0.000 <0.0005 There is a difference in the average score of the learning responsibility scale of 37.68% between the pretest and posttest on the results of the discussion and data analysis. The conclusion from the results of this research is that group counseling with behavioral rehearsal techniques has an effect on increasing student learning responsibilities in the Covid-19 pandemic era. Keywords: behavioral rehearsals; group counselin; learning responsibility